Effect of carboxymethylcellulose and locust bean gums on some of physicochemical, mechanical, and textural properties of extruded rice. Issue 1 (19th October 2020) - Mirzaei, Mehry; Movahhed, Sara; Asadollahzadeh, Mohammad Javad; Ahmadi Chenarbon, Hossein
Abstract: Extrusion is a composite process consisting of many different unit operations such as mixing, cooking, pasting, and molding. In this process, the raw material is forced through a tiny opening to be transformed into a product with a desired and unique shape, texture, color, and taste. In combination with different amounts and types of additives, this technique can result in functional food products for a broad range of people suffering from micronutrient deficiency. The hydrocolloid compounds are now employed to improve the texture and performance properties of many food products. Therefore, this study scrutinized the effects of carboxymethylcellulose and locust bean gums at different levels (0.5, 0.75, and 1%) alone or in combination with each other on chemical, physical, mechanical, and textural properties of extruded rice in comparison with the qualitative properties of the control rice. A completely random design was used along with three replications to analyze the test results. Then the means were compared through Duncan's multiple range test at (α = 5%). According to the results, addition of gums increased moisture, ash, total color difference, water absorption capacity, solubility, failure force, rupture energy, elasticity module, and toughness when reduced lateral expansion was compared to the control. Moreover, the addition of gums after the cooking process increased cooking loss, texture hardness, chewability, and elasticity of the specimens in comparison with the control. According to the results of pre‐ and post‐cooking tests, the specimens containing locust (0.75%) and carboxymethylcellulose (0.75%) gums were the best treatments.